Walking training and cortisol to DHEA-S ratio in postmenopause: An intervention study. Issue 4 (21st April 2018) - Di Blasio, Andrea; Izzicupo, Pascal; Di Baldassarre, Angela; Gallina, Sabina; Bucci, Ines; Giuliani, Cesidio; Di Santo, Serena; Di Iorio, Angelo; Ripari, Patrizio; Napolitano, Giorgio
ABSTRACT: The literature indicates that the plasma cortisol-to-dehydroepiandrosterone-sulfate (DHEA-S) ratio is a marker of health status after menopause, when a decline in both estrogen and DHEA-S and an increase in cortisol occur. An increase in the cortisol-to-DHEA-S ratio has been positively correlated with metabolic syndrome, all-cause mortality, cancer, and other diseases. The aim of this study was to investigate the effects of a walking program on the plasma cortisol-to-DHEA-S ratio in postmenopausal women. Fifty-one postmenopausal women participated in a 13-week supervised walking program, in the metropolitan area of Pescara (Italy), from June to September 2013. Participants were evaluated in April–May and September–October of the same year. The linear mixed model showed that the variation of the log10 Cortisol-to-log10 DHEA-S ratio was associated with the volume of exercise ( p  = .03). Participants having lower adherence to the walking program did not have a significantly modified log10 Cortisol or log10 DHEA-S, while those having the highest adherence had a significant reduction in log10 Cortisol ( p  = .016) and a nearly significant increase in log10 DHEA-S ( p  = .084). Walking training appeared to reduce the plasma log10 Cortisol-to-log10 DHEA-S ratio, although a minimum level of training was necessary to achieve this significant reduction.